Chapter 4 The mechanisms of social care reform - Needham, Catherine (Policy Press, 2023)
Chapter 4 and chapter 7 are available Open Access under CC-BY-NC-ND licence. Two decades have passed since the devolution of social care policy, with key differences emerging between the UK's four systems, but what impact have these differences had? This book presents for the first time research on the perspectives of social care policy makers on the four systems in which they operate and the ways in which they borrow from one another. Drawing on extensive interviews with national and local policy makers across the UK, the book raises vital questions about the role of 'standardisation' and 'differentiation' in social care, concluding that when given equal capacity to reform their respective systems, the regimes in each nation may take radically different shapes.